Influence of grain size and crystallographic orientation on microbially influenced corrosion of low-carbon steel in artificial seawater - Liu, Ruiliang (2024)
How the microstructure of steel affects a material's response to microbially influenced corrosion (MIC) in marine applications remains largely unclear, partly because of the challenge in mapping local structure–property relationships. Focusing on sulphate-reducing bacteria, the onset and rate of MIC on low-carbon marine steel samples were analysed with a wide range of grain size and as a function of the local surface crystallography using a combination of optical and electron microscopy, mass loss measurements, and electrochemical testing. It is shown that the alloy's resistance to MIC decreases with increasing in grain size. A significant effect of the local crystallographic orientation on the material's dissolution rate is also recorded, which is lowest along the 〈1 0 0〉 crystallographic orientation in this steel when exposed to artificial seawater. These findings outline a clear relationship between the microstructure and the susceptibility to MIC in marine steel, which may be used to design alloys with enhanced resistance to MIC in marine applications.